The Influence of Motivation, Work Environment and Compensation on Employee Performance: Case Study at PT. Marurat Artaraya - Irwan Nopian Sinaga (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to determine the effect of motivation, work environment, and compensation on employee performance at PT. Marurat Artaraya. The population in this study are employees of PT. Marurat Artaraya, totaling 145 people. While the technique of determining the sample using the solvin technique. This type of research is quantitative research. The data sources in this study are primary data and secondary data where the data has been processed from the internet, documentation, and journals. While the data analysis technique used is descriptive and multiple linear regression with hypothesis testing by t test, f test and coefficient of determination. The results of multiple linear regression analysis show Y = 2.467 + - 0.115X1 + 0.585X2 + 0.436 e. While the results of the test (t) or partial test show that motivation has a negative and insignificant effect on employee performance at PT. Marurat Artaraya, where it can be seen that the motivation value tcount is -1.797 > ttable 0.2201, the work environment has a positive and significant effect, it can be seen tcount is 6.043 > ttable 0.2201, while compensation has a positive and significant effect, it can be seen tcount is 3.774 > ttable 0.2201 on the performance of employees at PT. Marurat Artaraya. Then the results of the f test showed that simultaneously there was a positive and significant effect of motivational variables (X1), work environment (X2), and compensation (X3) on employee performance (Y) and the Fcount value was 156.871 > Ftable 3.16. Furthermore, the coefficient of determination (R2) in the adjusted R Square value is 0.890 (89.0%). So it can be said that 89.0% of the variation of the independent variables, namely motivation, work environment and compensation in this model has a contribution to the variable performance of employees at PT. Marurat Artaraya. While the remaining 11.0% is influenced by other variables outside the model.